2015
DOI: 10.1111/acem.12626
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Pediatric Emergency Department Care of Sickle Cell Disease and Fever

Abstract: Objectives: The objective was to study the variation in pediatric emergency department (PED) practice patterns for evaluation and management of children with sickle cell disease (SCD) and fever in U.S. children's hospitals. Methods:A cross-sectional study of visits by children 3 months to 18 years of age with SCD and fever evaluated in 36 U.S. children's hospital PEDs within the 2010 Pediatric Health Information System database. The main outcome measures were the proportions of SCD visits that received evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 20 publications
0
10
0
1
Order By: Relevance
“…Our data suggest that there is strong evidence to add chest pain to these high‐risk criteria, while a high WBC count and history of ACS can further identify patients at risk for ACS. Given the previously documented variability in practice, it is clear that data‐driven evidence is needed to further determine which patients require a CXR . While neither the NHLBI guideline nor our model identified all instances of ACS, our model provides additional evidence of high‐risk groups that might be more likely to benefit from obtaining a CXR.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Our data suggest that there is strong evidence to add chest pain to these high‐risk criteria, while a high WBC count and history of ACS can further identify patients at risk for ACS. Given the previously documented variability in practice, it is clear that data‐driven evidence is needed to further determine which patients require a CXR . While neither the NHLBI guideline nor our model identified all instances of ACS, our model provides additional evidence of high‐risk groups that might be more likely to benefit from obtaining a CXR.…”
Section: Discussionmentioning
confidence: 92%
“…The variables abstracted from the patient chart and these composites were compared between those with ACS and those without ACS using a chi‐square test for categorical variables (and Fisher's exact test where indicated due to small sample sizes) and a Wilcoxon rank‐sum test for nonparametric continuous variables with a Type I error rate of <0.05. Similar to previous studies, all visits were treated as independent occurrences for analysis . We performed binary recursive partitioning using classification and regression tree (CART) analysis to determine predictive factors for a diagnosis of ACS (CART PRO 6.0, Salford Systems) .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, we saw that visit‐level factors such as weekday versus weekend did not have a significant effect on fever admission variation. Similar to the admission variation seen in pain, other nonvisit‐level factors are more likely to be influencing this variation, as mentioned in previous studies . For example, social and environmental factors such as distance from a hospital with experience caring for patients with SCD, reliable transportation, and compliance may all play a role in determining disposition.…”
Section: Discussionmentioning
confidence: 54%
“…Fever, the next most common reason for a child with SCD to visit the ED showed much greater variation than overall or pain in admission percentages between hospitals, despite having established recommendations for hospitalization of children with fever by the NHLBI and the American Academy of Pediatrics (AAP) Section of Hematology/Oncology . Ellison et al using 2010 PHIS data demonstrated significant practice variation in ED care of fever in children with SCD even when controlling for patient‐level characteristics . A recent study also showed significant provider and hospital practice variation in SCD fever management in a retrospective review of three pediatric EDs .…”
Section: Discussionmentioning
confidence: 99%